The structure and dynamics of creative tourism: an ePortfolio approach - Bakas, Fiona (2023)
Contributing to limited knowledge of creative tourism product development and operationalization processes in small cities and rural areas, ePortfolios were used as an online fieldnote depository for photographs and texts, which were entered by geographically dispersed researchers within the CREATOUR research-and-application project. The ePortfolios, as a type of research diary, record and examine the ways in which 48 different creative tourism activities were structured, organized and implemented. The thematic analysis of this empirical data identified five temporally distinct organizational moments that comprise the creative tourism activities and reveal the nuances of active participation, learning and community engagement as key elements characterizing creative tourism activities. Findings indicate that creative tourism activities are fertile ground for the contemporary tourist trends of wanting to go beyond ‘gazing’ and to experience active involvement, which in these activities involved four different types of active participation. The ePortfolios also highlight the significance of the learning component within creative tourism, illustrating some ways in which learning is integrated into tourism activities. Links to the community are revealed with, for example, elderly women acting as artisan teachers, through which local participation is enabled and communication between visitors and residents is fostered. The use of ePortfolios as an ‘exploratory’ research platform and tool in tourism research is also discussed, for example, in terms of stimulating creative expression and offering researchers freedom to present discovered aspects that may not be captured in ‘pre-planned’ data forms and processes.